NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM KARYA DIAN PURNOMO DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Novita Dwi Prasasti; Ade Siti Haryanti; Suyekti Kinanthi Reje (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This his study aims to analyze and describe the values of character education in novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo and its implications for learning Indonesian. The research method used is decriptive qualitative method. The research technique used is content analysis technique. The results showed that there were 16 values of character education in novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo including religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, love for the homeland, appreciate achievement, friendly/communicative, love peace, love to read, social care, and responsibility. Overall data found as many as 189 character values. The most common character values were curiosity character values, which were 77 character values. Novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo can be used as teaching materials in Indonesian language learning in high school class XII, which is found in K.D. 3.9 analyze the content and language of the novel.